The role of matrix stiffness in hepatic stellate cell activation and liver fibrosis - Wells, Rebecca G (Journal of clinical gastroenterology, 2005)
Liver fibrosis results primarily from the action of hepatic stellate cells, nonparenchymal cells of the liver that undergo transdifferentiation into fibrogenic, proliferative, and contractile myofibroblasts. Stellate cell transdifferentiation has been modeled by the culture of primary cells, a system that has yielded important information about factors determining the phenotype of these cells. Recent evidence suggests that the growth factor TGF-beta (acting through the cytoplasmic signaling intermediate Smad3) and the mechanical properties of the underlying matrix play particularly important roles in hepatic stellate cell transdifferentiation and that this transdifferentiation is a multistep process. The interrelationship between TGF-beta and matrix stiffness and the implications of the in vitro findings for liver fibrosis are now the subject of intensive investigation and will likely lead to important insights into the diagnosis and treatment of liver disease.